A survey of Old Testament introduction - Archer, Gleason L. (Gleason Leonard), 1916-2004 (Chicago, Ill. : Moody Press, 1981)
A Survey of Old Testament Introduction has been an invaluable resource for students, scholars, and laypeople who want to understand the conservative position on the Old Testament and are not afraid to examine critical views. Recently updated with four-color charts, maps, and graphics, Gleason Archer's classic volume approaches the study of the Old Testament from both the general and specific points of view. - Back cover
Editor information from publisher website
Includes bibliographical references (p. 491-494) and indexes
Keywords: Bible. -- Introductions